Antiviral Action of Native and Methylated Lactoferrin and β-Lactoglobulin against Potato Virus Y (PVY) Infected into Potato Plants Grown in an Open Field - Mahmoud Sitohy; Soad Taha; Ali Osman; Mahmoud Abdel-Hamid; Ali Hamed; Ashraf Abdelbacki (MDPI AG, 2020)
Potato plants are liable to PVY infection without efficient control. Therefore, they were cultivated under greenhouse and open field conditions, artificially infected with PVY and then treated after 15 days of infection with native lactoferrin (LF) and native β-lactoglobulin (BL) and their esterified forms, MLF (methylated lactoferrin) and BLM (methylated β-lactoglobulin) to test the efficiency of this approach. Viral replication was inhibited by the applied substances, particularly the methylated forms, in a concentration-dependent manner, where the concentration of 500 μg·mL−1 was sufficient for plant protection against the PVY infection. An open field experiment showed that one single application of the antiviral substance was enough for maximum inhibitory action against PVY. The modified milk proteins induced higher inhibitory action on PVY virus replication in the plants, compared to their native forms, which was reflected by potato growth and yield. Using the dot blot hybridization and RT-PCR techniques to detect PVY in the experimental plants showed the supremacy of native and esterified LF in inhibiting the targeted virus. The generally observed scanning electronic microscopy (SEM) structural deformations and irregular appearance in PVY particles when treated with MLF and BLM revealed their direct action. BLM, MLF and LF are efficient antiviral agents against PVY. They can not only abolish the observed PVY-induced reduction in potato growth and tuber yield, but also further increase them to higher levels than negative control.